XANTHIUM STRUMARIUM L: BIOLOGICAL CHARACTERISTICS, PHARMACOLOGY, AND APPLICATION IN TRADITIONAL MEDICINE - Artiqov, M.B.; Xaytbayev, T.D.; Sabirov, А.S.; Khajibayev, Q.G.; Berdimbetova, G.E. (SCIENCE and SOCIETY, 2021)
The article describes the biological characteristics of the plant Xanthium strumarium L (X. Strumarium), which grows in Karakalpakstan. Based on the study of the database. There is given information the pharmacological properties, medicinal tinctures, methods of preparation of ointments, as well as ointments made from the fruit of X. Strumarium and its use in folk medicine are presented.
Keywords: Xanthium strumarium L; Pharmacological properties; tincture of leaves; ruit tincture; and root tincture